Pengaruh Resiko Bisnis, Profitabilitas Dan Pertumbuhan Aset Terhadap Struktur Modal - Rafi, Syahfri Amirul; Susyanti, Jeni; Priyono, Achmad Agus (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the effect of Business Risk, Profitability, and Asset Growth variables on Capital Structure in basic and chemical companies listed on the Indonesia Stock Exchange (IDX) during 2018–2021. The population consists of 73 basic and chemical companies that were and are still listed on the IDX in the 2018–2021 period. The sampling technique used is purposive sampling, resulting in a sample of 32 basic and chemical companies listed on the IDX for the 2018–2021 period. The data were analyzed using multiple linear regression, processed with SPSS 25 software. The data analysis methods include normality test, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R²). The results show that the business risk ratio has a negative and insignificant effect on capital structure. The profitability ratio has a positive and significant effect on capital structure. Meanwhile, asset growth has a negative and insignificant effect on capital structure. Keywords: Business Risk Ratio, Profitability Ratio, Asset Growth Ratio